The relationship between transfer of training and leadership styles with training effectiveness among non-academic staffs in Universiti Utara Malaysia - Jafri, Ishak (2014)
The main purpose of this study is to investigate the relationship between transfer of training and leadership style with training effectiveness among non-academic staff in Universiti Utara Malaysia. The objectives of this study is to examine the relationship between transfer of training, leadership style (Transactional leadership style and Transformational leadership style) and effectiveness of training. Data was collected through a survey of 273 respondents using the approach of quantitative research methods. Analysis of the quantitative data suggests that transfer of training and leadership style are significantly associated with effectiveness of training among non- academic staff in Universiti Utara Malaysia. Meanwhile for leadership style, it was found that transactional leadership is most significantly associated with effectiveness of training compared to transformational leadership. At the end of this study, recommendations have been given to the university as well as recommendations for future studies.